ISSUES OF FORMATION AND OPTIMIZATION OF THE MODERN COMPOSITION OF THE BALANCE OF PAYMENTS UNDER THE TRANSFORMATION OF THE WORLD ECONOMY (European Journal of Economics, Finance and Business Development, 2024)
The article talks about the issues of forming and optimizing the modern structure of the balance of payments of Uzbekistan in the context of the transformation of the world economy.